2017
DOI: 10.32601/ejal.461003
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceptions of the use of a YouTube channel specifically designed for an Academic Speaking Skills Course

Abstract: Advancements in information and communication technology have revolutionized the notion of teaching and learning in terms of strategies, context, and methods. One of the most remarkable tools used in teaching and learning in the 21st century is YouTube, especially in language education. The literature demonstrates the need for elaboration of the use of YouTube in university level language skills education settings. In the 2016-2017 academic year a YouTube channel with a variety of supplementary material videos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 13 publications
(12 reference statements)
6
45
0
2
Order By: Relevance
“…The data in Table 2 revealed that EFL learners have positive attitudes toward the use of social media in language learning, which is in line with the previous research with regard to the use of social media in general (Akhiar, Mydin, & Kasuma, 2017;Aloraini, 2018;Al-Qaysi, Mohamad-Nordin, & Al-Emran, 2019;Bailey, Park, & Haji, 2017;Balbay, & Kilis, 2017;Eaton, 2010;Elia, 2006;Fewell, 2014;Fleck, Beckman, Sterns, & Hussey, 2014;Kabooha, & Elyas, 2018) and the use of social media during the pandemic (Cheung, 2021;Serhan, 2020;Suadi, 2021) in particular. Some learners believed that social media could help them develop their vocabulary knowledge (Al-Qaysi, Mohamad-Nordin, & Al-Emran, 2019).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The data in Table 2 revealed that EFL learners have positive attitudes toward the use of social media in language learning, which is in line with the previous research with regard to the use of social media in general (Akhiar, Mydin, & Kasuma, 2017;Aloraini, 2018;Al-Qaysi, Mohamad-Nordin, & Al-Emran, 2019;Bailey, Park, & Haji, 2017;Balbay, & Kilis, 2017;Eaton, 2010;Elia, 2006;Fewell, 2014;Fleck, Beckman, Sterns, & Hussey, 2014;Kabooha, & Elyas, 2018) and the use of social media during the pandemic (Cheung, 2021;Serhan, 2020;Suadi, 2021) in particular. Some learners believed that social media could help them develop their vocabulary knowledge (Al-Qaysi, Mohamad-Nordin, & Al-Emran, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…In the EFL/ESL learning/teaching context, some researchers shed some light on different PSMs with regard to their uses, potentials, etc. including Instagram (Akhiar, Mydin, & Kasuma, 2017;Aloraini, 2018;Anggraeni, 2017;Gonulal, 2019;Mansor, & Rahim, 2017;Sari, & Wahyudin, 2019), YouTube (Balbay, & Kilis, 2017;Fleck, Beckman, Sterns, & Hussey, 2014;Kabooha, & Elyas, 2018;Maziriri, Gapa, & Chuchu, 2020), Facebook (Atmaca, 2013;Bailey, Park, & Haji, 2017;Çakır, & Atmaca, 2015;Shukor , 2015;Terantino, 2013), Twitter (Cheng, 2012;Kim, Park, & Baek, 2017;Mompean, & Fouz-González, 2016;Said, & Abd Elfatah , 2015;Taskiran, Gumusoglu, & Aydin, 2018), Skype (Eaton, 2010, Elia, 2006Ockert, 2015Ockert, , 2020Yen, Hou, & Chang, 2015), Zoom (Cheung , 2021;Khusniyah, 2020;Nuryanto, 2021;Serhan, 2020), and What's App (Hamad, 2017;Noorani, & Salehi, 2019;Suadi, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In language education, YouTube is one of the remarkable tools used in the learning process. It was the most used website ever since the internet was developed in the 1990s (Balbay & Kilis, 2017). For motivational purposes, teachers can use YouTube to show about the prospective jobs from and facts about mastering a foreign language.…”
Section: Visual Methods (Vm2)mentioning
confidence: 99%
“…The majority of participants stated that the use of social media enabled them to practice English skills, because they can make a discussion and communication both oral and written English language. After that, the using of social media also can be seen in any kind of activities in the class, since it is known that learning using social media can improve the knowledge of the students' especially in learning English (Balbay & Kilis, 2017). The activity that the participants can use social media in learning English is a discussion group.…”
Section: Discussionmentioning
confidence: 99%